The Seven Messages of Revelation and Vassal Treaties : Literary Genre, Structure, and Function - Graves, David E. (Gorgias Biblical Studies, 2014)
This book argues that the genre of the seven messages in Revelation 2-3 is a hybrid prophetic oracle. This oracle is influenced by the Old Testament covenantal elements functioning as a set of lawsuit exhortations. Graves defends this by demonstrating the influence of the Ancient Near Eastern vassal treaty structure in the seven messages. Written in a readable format this work is both an excellent introduction to the book of Revelation as well as a fitting work for the apocalyptic specialist.